Hereditary Angioedema: Three Cases Report, Members of the Same Family - Alexandros Kolokotronis; Paraskevi Tsirevelou; Apostolos Matiakis; Mattheos Papamanthos; Haralambos Skoulakis (eJournal of Oral Maxillofacial Research, 2010)
Background: This current clinical case report highlights three cases of Hereditary angioedema (HAE) patients who are all members of the same family (father and his two daughters). The father has C1–INH deficiency, while his daughters have low C1–INH levels: the first possesses only 10% function and the second has low C1–INH level with 0% function. Of note, the second daughter was discovered to have HAE at the age of 2, thus making her the youngest known HAE case report in the English literature.Methods: Assess the efficacy of administration of C1-INH before dental operation as regards the prevention of HAE episode, when total or partial C1-INH deficiency exists.Results: Acute angioedema leading to laryngeal oedema is a possibly fatal complication for HAE patients undergoing dental procedures. Use of both short-term and long-term HAE prophylaxis prior to dental operations might be life saving for those patients.Conclusions: Prevention and early recognition of potential laryngeal oedema that can occur as a complication of dental procedures may be lifesaving for HAE patients.